Inefectividad en la aplicación de boletas de apremio personal total con allanamiento por la falta de pago de pensiones alimenticias atrasadas, al no permitirse el descerrajamiento de las puertas. - Vicente Vega, Wester Daniel (2024)
The present work of curricular integration has been developed in view of the need to analyze and investigate the main cause that produces the ineffectiveness in the application of the total personal restraining orders with search warrant for the non-payment of alimony, starting from the fact that the current legislation specifically establishes adequate and consensual mechanisms to put pressure on those obliged to comply with the legal mandate to provide alimony in favor of a minor, However, in spite of the existence of legal mechanisms that allow the collection of overdue alimony, these do not include a very important aspect within the total personal restraint order, which would effectively help to execute this measure, and we are talking about what could be the unlocking of the doors of a real estate property or place where the debtor is located, and this would allow to execute the precautionary measure in an effective way. In view of this problem, we have made a legal and doctrinal study of the total personal restraining orders with search and seizure, with the purpose of analyzing this legal mechanism and at the same time find the reason that makes them ineffective and we have been able to determine that the judge when issuing these orders, only issues 17 them with search and seizure, but this term is not well understood within the national legal jargon, and although search and seizure means to enter by force to a certain place to fulfill a certain procedure, this is not complied with by the officers of the court, but it is not respected by the officers of the court, this is not complied with by the officials who comply with the order of constraint against the debtor under the argument that they cannot or do not have the power to break a lock or any other type of security mechanism, for fear of being sued for destruction of private property or violation of personal and/or family privacy, It is here where it becomes necessary and urgent the inclusion in the ballots, of the unlocking of the doors of the domicile or the place where the debtor of the pensions is, in order to achieve his compulsion and therefore the coercive force to cancel what is owed to his fed, and in this way the state and its agencies would be watching over and making effective the effective judicial protection and the constitutional mandate to protect the best interest of the child, it is evident the problem that is generated in the society especially to the mothers or representatives of the minors who go to the judicial apparatus in search of solving an urgent problem such as the survival of a minor and find themselves with an endless number of obstacles, of interposition of resources that do not fit in this type of procedures with the only objective of delaying the solution and attention to the obligation, It is of relative urgency perhaps a modification of the 8th paragraph in article 137 of the General Organic Code of Processes in which it should be in order to protect the right to life itself of a minor. For the exposed background is that we will conduct an investigation and analysis of this measure in which we seek to determine what are the factors that cause this lack of effectiveness, with the known detrimental effects to minors who should receive this type of support from their obligors.